Does Financial Literacy Drive Waqf Intention? Insights from Pesantren-Based Universities - Galih Aisia; Andika Rendra Bimantara; Fahmilia Rahmanita; Noora Fauzia Ghazali; Wahyu Puji Astuti (Journal of Islamic Contemporary Accounting and Business, 2025)
This study investigates the relationship between financial literacy and the intention to participate in waqf among lecturers and staff of Universitas Darussalam Gontor, a pesantren-based university. Using a quantitative research design with a deductive approach, data were collected through questionnaires distributed to a sample of 132 respondents selected via the Slovin method from a total population of 196 individuals. Regression analysis demonstrates that financial literacy has a positive and statistically significant effect on waqf intention, indicating that individuals with higher financial knowledge are more inclined to contribute to waqf. The findings provide empirical evidence that improving financial literacy can enhance philanthropic behavior and promote sustainable Islamic social finance. The study highlights the strategic role of pesantren-based universities in fostering waqf awareness through financial education programs. Implications of this research suggest the need for policymakers and educational institutions to integrate financial literacy into academic curricula and community initiatives to strengthen waqf participation as a sustainable instrument for social and educational development.